Analysis of Learning Motivation on Students Activities of Package C Equality Program in Nganjuk District - Eriyanto, Moh. Ghoizi; Roesminingsih, Maria Veronika; Soedjarwo, Soedjarwo (International Journal for Educational and Vocational Studies, 2021)
McClelland's theory of motivation focuses on three needs, namely the need for achievement, the need for power, and the need for affiliation. This study method uses quantitative research with descriptive method. This study aims to determine whether learning motivation has an effect on student activity. Sources of research data were obtained from 3 PKBM institutions in Nganjuk Regency. The data were analyzed using descriptive analysis to determine the activity of the experimental and control classes. Active Observation (Psychomotor and Oral Activities) the average activity value reached 85.23%. This percentage is included in the very good category. The t-test calculation of the activeness score shows tcount > ttable. So it can be concluded that there is an influence of learning motivation on the activity of students in PKBM Nganjuk Regency.